2019
DOI: 10.1097/md.0000000000014702
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reaction to platelet-rich plasma (PRP)

Abstract: Rationale:In the recent years, growing interest is focused on the use of platelet-rich plasma (PRP) in wound healing and tissue regeneration. There are a number of papers regarding the usefulness of PRP in the healing of ulcerations, skin injures, bone loss or distraction osteogenesis. Most authors emphasize the safety of PRP usage due to its authogenic nature.Patient concerns:We present a case of a 14 -year-old boy admitted to our department due to simple bone cyst of the distal tibia, qualified for injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…Extrapolation of our findings to the clinic might explain the inflammatory reactions observed in patients after receiving regenerative and local treatments with PRP (Bowman et al, 2013;Kaux et al, 2014;Alam et al, 2018;Latalski et al, 2019). These complications were not associated with the presence of leukocytes in PRP since all the interventions were performed using free-leukocyte PRP.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Extrapolation of our findings to the clinic might explain the inflammatory reactions observed in patients after receiving regenerative and local treatments with PRP (Bowman et al, 2013;Kaux et al, 2014;Alam et al, 2018;Latalski et al, 2019). These complications were not associated with the presence of leukocytes in PRP since all the interventions were performed using free-leukocyte PRP.…”
Section: Discussionmentioning
confidence: 62%
“…The studies about the effect of anticoagulants in the context of regenerative treatments with platelets are only focused on optimizing platelets number, coagulation or platelet-derived growth factors levels (O'Neill et al, 2001;Giraldo et al, 2015;do Amaral et al, 2016;Gonzalez et al, 2016;Singh, 2018) but they do not analyze the functionality of platelets on target tissue neither the possible adverse consequences caused by anticoagulants additives in platelet solutions. Notably, adverse effects have been reported in patients in the context of tendinopathies treatments with PRP including swelling, erythema, edema, and pain (Bowman et al, 2013;Kaux et al, 2014); skin redness, swelling, bruising, pruritus, scaling, and dryness after intradermal injection of PRP in the context of skin rejuvenation (Alam et al, 2018); and the systemic allergic reaction postinjection of PRP into a bone cyst (Latalski et al, 2019). Although the potential mediators/mechanisms involved in these effects were not addressed, one of these studies revealed the intradermal allergic reaction against citrate during skin allergic test (Latalski et al, 2019) suggesting a possible toxic effect caused by the anticoagulant additive in PRP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this regard, there are not well-designed prospective studies that would address this aspect in a rigorous manner, including all clinical applications. The use of L-PRP (containing leukocytes) or fresh PRP may predispose to this type of reactions because living cells (not only white or red blood cells, but also platelets themselves) might exacerbate basal inflammation at the site of application, considering the novel functions of platelets beyond haemostasis (72)(73)(74)(75).…”
Section: Clinical Uses Of Platelet-derived Bio-products and Concerns:mentioning
confidence: 99%
“…61 The current literature is very limited regarding treatment-related complications following PRP, so further studies are needed. 62 Interest in the use of PRP injections for use in the face has been growing due to the ability to provide volume fill and high concentrations of growth factors. Injection of PRP however has had mixed results within small-scale studies.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%